2017
DOI: 10.3389/fphar.2017.00423
|View full text |Cite
|
Sign up to set email alerts
|

A Single Dose of LSD Does Not Alter Gene Expression of the Serotonin 2A Receptor Gene (HTR2A) or Early Growth Response Genes (EGR1-3) in Healthy Subjects

Abstract: Rationale: Renewed interest has been seen in the use of lysergic acid diethylamide (LSD) in psychiatric research and practice. The repeated use of LSD leads to tolerance that is believed to result from serotonin (5-HT) 5-HT2A receptor downregulation. In rats, daily LSD administration for 4 days decreased frontal cortex 5-HT2A receptor binding. Additionally, a single dose of LSD acutely increased expression of the early growth response genes EGR1 and EGR2 in rat and mouse brains through 5-HT2A receptor stimulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 52 publications
0
8
0
Order By: Relevance
“…As of today, investigations on psychedelic-induced (epi)genetic modifications in humans are scarce. One clinical study with 15 subjects did not find any alterations in expression of the HTR2A or EGR1-3 genes 1.5 and 24 h after administration of 100 μg LSD compared with placebo [102]. Rodent studies, however, consistently show a widespread upregulation of different genes and their translation into proteins, primarily those involved in synaptic plasticity, neural signaling, and memory, in various brain regions (including the cortex, amygdala, nucleus accumbens, and striatum) after LSD and DOI exposure [101,103,104].…”
Section: Epigenetics Modificationsmentioning
confidence: 96%
See 1 more Smart Citation
“…As of today, investigations on psychedelic-induced (epi)genetic modifications in humans are scarce. One clinical study with 15 subjects did not find any alterations in expression of the HTR2A or EGR1-3 genes 1.5 and 24 h after administration of 100 μg LSD compared with placebo [102]. Rodent studies, however, consistently show a widespread upregulation of different genes and their translation into proteins, primarily those involved in synaptic plasticity, neural signaling, and memory, in various brain regions (including the cortex, amygdala, nucleus accumbens, and striatum) after LSD and DOI exposure [101,103,104].…”
Section: Epigenetics Modificationsmentioning
confidence: 96%
“…Considering the described neural regional specificity of changes in gene expression observed in animal studies, it is questionable how meaningful the respective results from human studies might be. This methodological weakness of clinical epigenetic studies could also be the reason for the null result reported by Dolder et al [102].…”
Section: Epigenetics Modificationsmentioning
confidence: 99%
“…It was recently reported that microdoses of LSD increase circulating BDNF levels in healthy volunteers, suggesting that LSD might have neurotrophic effects in humans . Another study investigated whether LSD produces acute gene expression changes in peripheral blood mononuclear cells 1.5 and 24 hours after administration, with no detected changes in 5-HT2A receptor or EGR-1, -2, and -3 transcript levels (Dolder et al, 2017a). In rodents, LSD upregulates CCAAT/enhancer-binding protein-b in the prefrontal cortex (Nichols and Sanders-Bush, 2004).…”
Section: B Effects Of Psychedelic Compounds On Neuronal and Synaptic Plasticitymentioning
confidence: 99%
“…For example, egr-2 expression was increased in rat cortical tissue cultures after LSD (10 μM), but not lisuride (10 μM), treatment ( González-Maeso et al, 2007 ), though in a human study, LSD (100 μg p.o.) failed to alter expression of egr-1, -2, or -3 in peripheral blood at 1.5 or 24 h after ingestion ( Dolder et al, 2017 ). Thus, while gene activation studies offer a valuable means to identifying long-term effects, results should be interpreted with careful consideration.…”
Section: Theories For Persisting Effects Of Classic Serotonergic Psycmentioning
confidence: 99%